N-Benzyl-2-(2-chloro-5-methylphenoxy)acetamide - Li, Zhu-Bo (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(16)H(16)ClNO(2), contains two crystallographically independent molecules, which differ mainly in the orientation of the benzyl group with respect to the rest of the molecule. In the crystal packing, centrosymmetrically related molecules are linked into dimers via intermolecular C—H⋯O hydrogen-bond interactions.